Optimizing Methane Production from Anaerobic Digestion of Dairy Cow Manure: The Potential Use of Carica (Carica pubescens) Seeds as a Co-Substrate - Purwasih, R.; Saindah, M.; Triyuwanti, H.; Yusuf, F. S.; Purnomoadi, A.; Purbowati, E.; Sutaryo, S. (Faculty of Animal Science, IPB University, 2025)
A method to increase methane production in dairy cow manure (DCM) is to co-digest DCM with nutritious biomass. This study aimed to determine the methane yield during the anaerobic co-digestion of DCM and carica seeds meal (CSM). Four continuous stirred tank reactors were operated with treatments P0 (100% DCM), P1 (98% DCM and 2% CSM), P2 (96% DCM and 4% CSM), and P3 (94% DCM and 6% CSM). The results demonstrated that the presence of CSM as a co-substrate of DCM significantly increased (p<0.05) methane production. The average methane production resulting from P0, P1, P2, and P3 in units of mL/g substrate and mL/g volatile solid (VS)added were 10.05, 20.54, 32.26, and 19.29 mL/g substrate and 171.49, 278.96, 357.92 and 179.30 mL/g VSadded, respectively. Thus, the highest methane production was obtained at P2. Treatment P3 contained a substrate containing excessively high protein and organic content, negatively affecting anaerobic microorganisms’ activity. The presence of CSM as a co-substrate enhanced methane production by 91.94%–221.06% compared with the control. The presence of CSM as a co-substrate significantly increased (p<0.05) volatile fatty acid and total ammonia nitrogen (TAN) concentrations and the pH of digested slurries but did not affect VS reduction. The co-digestion of DCM and CSM must consider the proportion of organic material in the mixed substrate. In this study, the mixed substrate with a VS proportion of 51.68% was the best-mixed substrate.